(untitled) (Archives of Pediatrics of Uruguay, 2021)
Acquired long QT syndrome may be secondary to hypothermia, both accidental and therapeutic. There is not enough knowledge about the effect of hypothermia in cardiac activity and its potential complications, especially in newborns. We present the clinical case of a newborn with a diagnosis of hypoxic ischemic encephalopathy who has a prolonged QT interval during treatment with hypothermia. The evolution of the patient is discussed, which is consistent with what is referred to in the literature on the subject: Good evolution, absence of serious arrhythmias or hemodynamic alterations, and normalization of the ECG after the end of treatment.